Trainability of players from the Bulgarian youth national field hockey team - Bonova, I. (Trakia Journal of Sciences, 2020)
PURPOSE: The aim of the study is to determine the sensitive windows related to motor skills development as well as the rate of trainability of the adolescent hockey players from the Bulgarian Youth National Field Hockey Team. METHODS: This study included 20 adolescent field hockey competitors at the national level - boys at an average age of 13.5 years. The experiment was conducted twice with the same participants at an interval of 16 weeks. They were assigned into two groups: responsive and non-responsive. Those who achieved an improvement in two or more motor tests were included in the "responsive" group. Those who did not improve their performance in the motor tests were included in the group of "nonresponsive" players. RESULTS: The findings from the study show that considering the age (13.5), aerobic and anaerobic conditioning is trainable (VO2max and 30 m speed test). DISCUSION: The responsive group was determined to be of high and slow trainability, while the nonresponsive one - of low and slow trainability, hence the prospects of the latter for staying in the national team are not favorable. CONCLUSION: It can be recommended that the head coach select only players of medium level trainability for the 2020 Summer Championship.